ASSESSING DESCRIPTIVE PARAGRAPH WRITING ABILITY OF THE EIGHTH GRADE STUDENTS OF SMPN 2 DENPASAR THROUGH DICTO-COMP - Ni Putu Santhi Widiastuti; I Made Sukamerta; Anak Agung Putu Arsana (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2020)
Writing is a productive skill in which each sentence should be organized to make meaningful writing. The English teacher of SMPN 2 Denpasar commonly used closedended test providing two different descriptive paragraphs and the students differentiate it. However, the test was quite simple and easy for the eighth grade students and it tended to assess reading. The present study aimed to figure out the descriptive paragraph writing ability of the eighth grade students of SMPN 2 Denpasar in academic year 2018/2019 through dicto-comp. The research used ex post facto research design with descriptive analysis. The population was the eighth grade students of SMPN 2 Denpasar totaling 333 students. There were 50 samples determined by using simple random sampling technique with lottery system. The obtained data were analyzed by using norm-reference measure of five standard value. The result showed that there were 72.00% of the samples who were successful and 28.00% of the samples under study were still unsuccessful in writing descriptive paragraph assessed by using dicto-comp.